Manajemen Pengorganisasian dan Personalia ( Penelitian di Madrasah Aliyah Raudlatul Muta’allimin Pangauban Pacet Kab. Bandung) - Neni Nurlaela (al-Afkar, Journal For Islamic Studies, 2020)
Organizing and personnel management is one of the most important parts in the management of educational institutions. Organizing and personnel management theories are important to run in educational institutions in order to realize organizational goals. this research aims to determine and identify the application of organizing and personnel management at Islamic High School Raudlatul Mut’allimin, which is located in Pangauban Village, Pacet District, Bandung. In this research, using qualitative approach and descriptive method. This source of information is the Head of Madrasah, the teachers and employees of the Islamic High School. Data collection techniques through observation, interviews and document analysis. The results of this research showed that Organizing and personnel management at Islamic High School Raudlatul Muta’allimin is carried out through planning by setting direction and goals, setting targets, formulating who will carry out tasks, setting priority positions, identifying various problems and needs and setting criteria in the recruitment of personnel. The implementation is by creating an organizational structure, assigning personal assignments and assigning tasks and programs. As for the supervision carried out intensively, both daily monitoring, supervision, monthly meetings and meetings that are incidental. In its application, organizing and personnel management can’t be used effectively and efficiently at this Islamic High School. It identifies the need for improvements internally in many ways, including in the organizational structure, division of labor, coordination, communication and others.